Some aspects of the tax burden - Kucherkova, Svitlana; Кучеркова, Світлана Олександрівна; Кучеркова, Светлана Александровна (My University, 2019)
The imperfection of the tax administration mechanism, despite all the innovations and reform measures, leads to an increase in the tax burden on business entities, citizens and society as a whole. The high level of tax burden reduces economic activity, promotes the movement of capital abroad, and slows the growth rate of gross domestic product. All these problems determine the relevance of the chosen research problem. The purpose of the paper is to study theoretical and methodological aspects of determining the tax burden, analysis of the impact of tax burden on the activities of economic entities, the formation of prospects for optimizing tax burden in the light of international experience.
Keywords: tax administration; economic activity